Peran Micro Teaching dalam Peningkatan Kompetensi Calon Guru Ekonomi: The Role of Micro Teaching in Improving the Competence of Prospective Economics Teachers - Shalikha, Putri Ayu Anisatus (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
This study investigates how the role of micro teaching courses provides valuable experience to prospective economics teacher students and reveals how students' efforts to improve their competencies as provisions for becoming teachers through micro teaching courses. This study was conducted at Universitas PGRI Wiranegara, Faculty of Pedagogy and Psychology, Economics Education Study Program, specifically on students of the 2021 intake who are currently taking semester 6. This study adopted a case study approach, using semi-structured interviews, Focus Group Discussions (FGDs), and observations for data collection. The findings show that all students of the 2021 intake who were the subjects of this study stated that they practiced at least four skills in micro teaching lecture activities. The first skill is the ability to manage learning, the ability to carry out responsibilities as prospective teachers according to the professional code of ethics and oriented towards students, the ability to communicate and interact effectively and efficiently, and no less importantly, the ability to master economics subject matter comprehensively. This study concludes that prospective economics teacher students can hone and combine pedagogical, personality, social, and professional competencies through micro teaching courses. Given the limitations regarding the generalizability of this research, it is recommended that future research collect more comprehensive data in relation to the depth of reflection and feedback in the education of prospective economics teachers through Introduction to School Environment courses or teaching assistantships in schools.